What is the evidence for the impact of ocean warming on subtropical and temperate corals and coral reefs? A systematic map - Man Lim Ho; Malgorzata Lagisz; Shinichi Nakagawa; Sarah Perkins-Kirkpatrick; Paige Sawyers; Charlotte Page; Bill Leggat; Troy Gaston; Alistair J. Hobday; Zoe Richards; Tracy Ainsworth (Environmental Evidence)
Abstract Background Subtropical coral reefs are comparatively understudied compared to tropical coral reef ecosystems, yet also host a diverse and abundant array of marine life and provide substantial socio-economic benefits to communities. Research into the impacts of ocean warming on subtropical coral reefs has increased over the past two decades due to increase frequency and intensity of bleaching and degradation of these ecosystems. Understanding the extent of research effort and type of evidence assessing the response of subtropical corals and reefs to ocean warming provides valuable insight into global patterns in research efforts allowing critical knowledge gaps to be identified. A comprehensive understanding the impact of ocean warming on these systems will underpin our ability to predict and respond to future changes on subtropical coral reefs. Here, a systematic-map approach is used to identify recent research effort, from 2010 to 2023, and highlight patterns in the type, scale, and location of research conducted and as well as identify the availability of data and evidence reported. Methods Primary literature was identified by searching Scopus and Science Citation Index Expanded through Web of Science Core Collection databases. The methodologies provided in a previously published systematic map protocol were applied, and 90 primary research publications were subsequently identified. Data extraction from the identified literature included bibliometric data, discipline and type of research, type of data reported and how it was recorded, and data availability. Findings The identified literature consisted primarily of experimental (49%) and observational (39%) studies. The majority of the primary literature investigated corals in the ecoregions of Southern China (13%), Western Mediterranean (10%) and across a total of seven ecoregions grouped within Oceania (29%). Stressors reported in the literature as drivers of ocean warming reflect the standardisation of methods applied in reporting of events within the literature. Standardised metrics related to degree heating weeks (DHW) and marine heatwaves (MHW) have been reported when assessing the occurrence and severity of drivers, and are increasing in recent years, particularly in Australia. Finally, the need for increased research effort across much of the subtropics is evident, particularly for understudied regions such as the Western Indian Ocean where there are far fewer studies than other similar subtropical coral reef ecosystems. Conclusions Climatic change, increasing ocean temperatures, and the impacts to subtropical and temperate coral reefs are of increasing concern to policy makers and researchers alike. This systematic map provides a broad overview of research topics and effort around the globe since 2010 and identifies areas where more research effort is urgently needed. Our study has identified major research clusters in Asia, Australia, the Mediterranean, and North America and gaps of research in regions such as the East Indian Oceans. Of the research conducted to date approximately one third reports on evidence related to marine protected areas and the vast majority of evidence is from close/territorial sea locations, providing important knowledge base for management of these areas. Of the 17 studies reporting on specific extreme events (rather than experimental studies which is the majority of evidence identified here) 13 have been published since 2019, with the majority reporting on events occurring in 2019/20 indicating a trend of increasing evidence in recent years (a total of 7 studies from 2010 to 2013, compared to over 10 studies published annually since 2019 up to mid-2023).